A study of acute toxicity of newly synthesized compound on adult hydrobiont Danio rerio - A. A. Safonov; Yu. V. Karpenko; Ye. H. Knysh (Zaporozhye State Medical University, 2021)
From ancient times the people used different poisons as a treatment for diseases of different genesis. To date, almost nothing has changed. One of the main conditions for the development of a new drug is its low toxicity. Literature analysis has shown that 1,2,4-triazole-3-thione derivatives are low-toxic compounds and exhibit a wide range of pharmacological activities. The aim of this work was the investigate acute toxicity LC50 in vivo of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate on the Zebrafish (Danio rerio) aquatic model according to OECD instruction № 203. Materials and methods. Determination of acute toxicity LC50 of the test compound was performed in vivo on a model of the aquatic organism Zebrafish (Danio rerio) according to the instruction OECD № 203 (Fish, Acute Toxicity Test) for testing chemical compounds (acute toxicity test on fish from 10.12.2009). It was used fish 2 months of age, 11.8 ± 0.1 mm long, and weighing 2.6 ± 0.2 g in the experiment. The concentration of the test compound ranged from 5.0 mg/l to 100.0 mg/l. Test water-soluble compounds were dissolved in distilled water. Each mini-aquarium with a certain dose of the compound contained at least 7 individuals of Danio rerio. During the experiments, the fish were kept on a diet for a test 96 hours and their mortality was checked every 24, 48, 72 and 96 hours. Statistical analysis of the results was performed using the program Statistica 6. Results. According to the obtained data, graphs of the dependence of the concentration on the fish mortality percentage were constructed. Then the corresponding values of LC50 sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate were calculated. According to the acute toxicity of LC50 (96 hours) of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate, which according to the classification of D. R. Passino and co-authors allowed it to be classified as a moderately toxic compound. Conclusions. The acute toxicity LC50 in vivo of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate on the Zebrafish (Danio rerio) aquatic model was investigated. The research was conducted in accordance with the national "General Ethical Principles of Animal Experimentation" approved by the First National Congress on Bioethics and the "Bioethical Expertise of Preclinical and Other Animal Research". The highest fish mortality occurs on the last day of observation (96 hours). The highest number of Zebrafish deaths is at a minimum concentration of the substance. The acute toxicity LC50 (96 hours) of the test substance was 4.5364 mg/l.